O protagonismo de gestores de restaurantes comerciais no contexto da vigilância sanitária dos alimentos - Almeida, Camila de Sousa [UNIFESP] (2016)
The increasing number of meals produced outside home has been raising the concern on foodborne diseases, due to their high incidence in restaurants. Because it represents a public health problem, a lot of effort has been applied to its control and among them Health Education stands out. The objective of this study was to carry out an educational action, in the context of Health Inspection for restaurant management based on the understanding of food safety practices, in order to investigate how the management reported knowledge is applied in practice. In order to do so a descriptive, quantitative and qualitative research-action method based on the CVS 05/2013 inspection script ordinance study was developed, having as its characteristic the collection of data considering different locales, actors and times. The study was carried out in restaurants (n=17), having their management as participants (n=24) and being contextualized in different stages: data analysis for sample delimitation; study presentation to the Health Authorities and establishment managements; health inspections (management self- evaluation, inspections prior and post educational action); an educational action on safe food preparation in restaurants, specifically devised for the restaurant management; management evaluation on the influence of this study and finally an intellectual product development. It was possible to collect data with different perspectives on the influence of health education and health inspection in the management of the studied establishments by the means of the quantitative instruments (restaurant/management registration IDs; health inspection scripts, structured questionnaires on the course themes) and qualitative (a course audio and an open questionnaire on the study stages).The results have shown an average risk perception when inquiries were about the peers and a low-risk perception when the inquiries were about management themselves. All the results have demonstrated an optimistic bias. Regarding sanitary inspection, prior and post the educational action, the results have shown that it collaborates to sensitize management but that is not thoroughly reflected in their practices. Considering the aforementioned practice (questionnaire prior and post course) and that observed (prior and post course inspections), the subject cross-contamination has stood out having obtained the highest level modification. During the courses, some intellectual productions were developed: an educational action plan and instructional material for restaurant management, a reflective action plan on inspection practices and health inspection script descriptors.By the means of this study, it was possible to conclude that there is a need for actions that promote the recognition of the management as the protagonists of the (re) significance of the actions stimulated by the reflections on safe practices in food handling in the daily life of his restaurant.